Logrolling-Prozess: Theorie und formale Darstellung einer verhandlungsunterstützenden Methode - N., N.

Stability in two-sided matchings with asymmetric information - N., N.

Sincere and Sophisticated Players in Matching Markets - N., N.

Mechanismen zur Informationsgewinnung in Verhandlungen - N., N.

Die faire Verteilung unteilbarer Güter - N., N.

Axiomatisierungen des Banzhaf-Wertes - N., N.

Compatibilities in Matching Mechanisms - N., N.

Faire Aufteilung von unteilbaren Gütern: Untersuchung von Algorithmen auf Effizienz und Neidfreiheit - N., N.

Anwendung und Vergleich von Verhandlungslösungen auf das Netzwerk-Design-Problem - N., N.

Verhandlungen mit Intermediären in IT-Märkten: eine spieltheoretische Analyse - N., N.

A bargaining model for relative profit and market share delegation contracts - N., N.

Wettbewerb in Märkten für Dienstleitungen mit uninformierten Kunden - N., N.

Der Shapley-Wert als Index für phylogenetische Diversität - N., N.

Student's school matching mechanisms in the US - N., N.

Conception of a digital Sales Bonus System based on Blockchain Technology - N., N.

Investigation of ductility and fracture behavior of EN AW-5182 H18 at non-isothermal forming conditions - Camberg, Alan Adam; Striewe, Marius; Tröster, Thomas; Bohner, F.; Tölle, J. (5th MATFEM Conference)

Modelling Relative Clauses in Processability Theory using Lexical Functional Grammar - Nottbeck, Emilia (Widening contexts for Processability Theory: Theories and issues)

Die Externsteine in der Kunstvermittlung: eine Studie zur regionalen Kulturerbebildung - Eikermann, Larissa
Keywords: Externsteine; Regionalkultur; Kunstvermittlung

Analyse und Optimierung des Korrosions- und Alterungsverhaltens von hybriden Strukturen aus Metallen und CFK - Striewe, Jan André; Tröster, Thomas; Kowatz, Jannik; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido

Analyse und Optimierung des Korrosions- und Alterungsverhaltens von hybriden Strukturen aus Metallen und CFK - Grothe, R.; Striewe, Jan André; Kowatz, Jannik; Grundmeier, Guido; Tröster, Thomas; Meschut, Gerson

Der Nichtmuslim zwischen dem Dhimma-Status und Muwâtana-Prinzip - Abdelrahem, Mohammed (Islam und religiöser Pluralismus, Grundlagen einer dialogischen muslimischen Religionstheologie)

Religionskooperativer Religionsunterricht- Bekenntnisse im Dialog: Unterrichtspraktische Verschränkung Komparativer Theologie und religionsdidaktischer Ansätze - Kamcili-Yildiz, Naciye; Konsek, Lukas (Heterogenität und Inklusion, Reflexionen und Anwendungen für die Religionspädagogik)

Islamic Studies in the West from Orientalism to Theology: Germany as a Model - Abdelrahem, Mohammed (Islam in the West)

Ritual and Rationality in Islam: A Case Study on Nail Polish - Mustafa, Abdul Rahman (Islamic Law and Society)

Illumination and Numbering. Function and Implication of Verse Markers in Early Qur'anic manuscripts from the National Museum of Iran - Aghaei Abrandabadi, Seyed Ali (Rechtes Maß und Heilige Zahl)

The Project “Irankoran”: Digitalisation of Early Quranic Manuscripts Kept in Iranian Collections - Aghaei Abrandabadi, Seyed Ali (The 9th European Conference of Iranian Studies (ECIS9))

Vulnerabilität - Ein vernachlässigter Aspekt muslimischer Theologie und Anthropologie - Tatari, Muna (Religionen unterwegs)

Textaufgaben lesen und verstehen lernen – Entwicklungsforschungsstudie zur mathematikspezifischen Leseverständnisförderung - Dröse, Jennifer

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Scaffolding für fachbezogene textsortenspezifische Lesestrategien – Entwicklungsforschungsstudie zur Förderung des Umgangs mit Textaufgaben - Dröse, Jennifer; Prediger, Susanne (Fachunterricht, Sprachbildung und Sprachkompetenzen)

Rah-e-halli Mu’menaneh Barai-e Zist Dar Donya-ie Modern: Tahlili bar Goftogoi-e Adyan (The Believers Solution to Living in the Modern World: An Analysis of Inter-religious Dialogue) - Haghani Fazl, Mohammad; Sadeghnia, Mehrab (Ma’rifat-e Adyan, 10)

Flexible Hot Rolling of Extruded Shapes of Aluminum Alloy EN AW-6082 - Grydin, Olexandr; Sotirov, Nikolay; Samsonenko, Andrii; Biba, Nikolay; Andreiev, Anatolii; Stolbchenko, Mykhailo; Behr, Teresa; Frolov, Iaroslav; Schaper, Mirko (Materials Science Forum)
One of the strategies employed to lower weight and to decrease material consumption is reducing part thickness itself. Thus, functionally graded materials in which structural reinforcement is adjusted locally, are of great interest. With regard to conventional industrial processes, such as extrusion or flexible cold rolling, thickness variations can only be achieved either longitudinally or through the cross-section of the semi-finished products. Hence, a combined thickness variation (along both axes) is difficult to generate solely by extrusion or rolling. A simultaneous thickness variation in both directions, however, would enable further weight savings in structural components such as car body parts. In this study, a promising approach with extruded shapes, serving as a billet for a flexible hot rolling process, is elaborated upon. By employing the described process modification, shapes with simultaneous thickness variations in longitudinal as well as in transverse direction are feasible. Initial numerical analysis reveals the weight-saving potential of using these semi-finished products for structural parts in a car body. A demonstration of the production process for the semi-finished parts and the occurring challenges are discussed. To verify and adjust the new technology, a numerical model of the flexible hot rolling process has been created based on the finite element software QForm VX. This model is also employed for tool design optimization to produce semi-finished components with the required geometrical quality. Finally, the results of hot rolling experiments conducted using the adjusted roll design are presented.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; General Chemistry; Bioengineering

Short austenitization treatment with subsequent press hardening: Correlation between process parameters, microstructure and mechanical properties - Grydin, Olexandr; Andreiev, Anatolii; Holzweißig, Martin Joachim; Rüsing, Christian Johannes; Duschik, Kristina; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)

Relationships between Microstructural and Mechanical Performance on Example of an Air‐Hardening Steel - Grydin, Olexandr; Andreiev, Anatolii; Zogaj, Mergim; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Beschleuniger-Experimente mit sichtbarer Spur der Elektronen - Eine Unterrichtsreihe in der Teilchenphysik - Bechstein, Stefan; Stahl, Achim; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Profile-P+: Kompetenz und Performanz im Lehramtsstudium Physik - Vogelsang, Christoph; Riese, Josef; Borowski, Andreas; Kulgemeyer, Christoph (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Erfassung der Fähigkeit zur Unterrichtsplanung im Physikunterricht - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Konzeption eines Lernzirkels zu experimentellen Kompetenzen - Goertz, Simon; Klein, Patrick; Riese, Josef; Heinke, Heidrun (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Die Veränderung physikdidaktischen Wissens im Lehr-Lern-Seminar - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschütter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan (Student Learning Outcomes Assessment in Higher Education – Perspectives, Concepts and Approaches for Research, Transfer and Implementation (KoKoHs Working Papers, 12))

Development of Prospective Physics Teachers’ Pedagogical Content Knowledge While preparing for an Internship - Joswig-Käfer, Ann-Kathrin; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Assessing Student Teachers‘ Skills to plan Physics Lessons - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Didaktische Rekonstruktion der Beschleunigerphysik und Entwicklung eines Lehr-Linearbeschleunigers - Bechstein, Stefan; Stahl, Achim; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Veränderung des physikdidaktischen Wissens im Verlauf eines Lehr-Lern-Seminars - Joswig, Ann-Kathrin; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Professionswissen von Physiklehramtsstudierenden in Österreich - Krumphals, Ingrid; Riese, Josef (Forschungsperspektiven 11: Lehrerinnen und Lehrerbildung in der Sekundarstufe)

Know your analysis: how instrumentation aids understanding static analysis - Schubert, Philipp; Leer, Richard; Hermann, Ben; Bodden, Eric (Proceedings of the 8th ACM SIGPLAN International Workshop on State Of the Art in Program Analysis - SOAP 2019)

Frühe mathematische Bildung im elementarpädagogischen Alltag - Bruns, Julia; Eichen, L. (KiTa aktuell Österreich)

VimaS_num: Measuring situational perception in mathematics of early childhood teachers - Bruns, Julia; Gasteiger, Hedwig (Proceedings of the 43rd Conference of the International Group for the Psychology of Mathematics Education)

Mathematical pedagogical content knowledge of early childhood teachers: a standardized situation-related measurement approach - Gasteiger, Hedwig; Bruns, Julia; Benz, Christiane; Brunner, Esther; Sprenger, Priska (ZDM)

Mathematikdidaktischen Wissen von frühpädagogischen Fachkräften aus kognitiv-situationsbezogener Perspektive – Theoretisches Konstrukt und empirische Erfassung - Bruns, Julia; Gasteiger, Hedwig (Beiträge zum Mathematikunterricht 2019)

Selbst erstellte Skizzen beim mathematischen Modellieren: Ergebnisse einer empirischen Untersuchung [Self-generated drawings for modelling problems: Findings of an empirical study] - Schönherr, Johanna

Sprachentwicklung und Aufbau sozialer Netzwerke von Jugendlichen mit Fluchterfahrungen: Zur Wirksamkeit von Angeboten zur Förderung von Sprache und gesellschaftlicher Integration - Schemmer, Susanne Jutta; Heisler, Dietmar (Berichte zur Beruflichen Bildung. Berufliche Integration durch Sprache)

Abraham soll seinen Sohn opfern - Aghaei Abrandabadi, Seyed Ali (Koran erklärt. Wichtige Verse kurz und verständlich erläutert)

Jointly Learning from Social Media and Environmental Data for Typhoon Intensity Prediction - Zahera, H.M.A; Sherif, Mohamed Ahmed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 10th International Conference on Knowledge Capture)

Struktur und Dynamik – Un/Gleichzeitigkeiten im Geschlechterverhältnis
Die gegenwärtige widersprüchliche Dynamik in der Veränderung von Geschlechterverhältnissen ist in ihrer Komplexität nur schwer zu greifen: Anzeichen für einen Bruch mit überkommenen Geschlechterkonzeptionen stehen neben Hinweisen auf (Re)Traditionalisierungstendenzen. Die Beiträge des vorliegenden Bandes diskutieren diese Entwicklungen aus unterschiedlichen Perspektiven und entlang unterschiedlicher gesellschaftlicher Bereiche. Sie sind das Resultat eines längeren Arbeitsprozesses der beteiligten Autorinnen, dessen Ergebnisse sie hier zur Diskussion stellen.

Parameterised Complexity of Abduction in Schaefer’s Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Logical Foundations of Computer Science)

Water adsorption and capillary bridge formation on silica micro-particle layers modified with perfluorinated organosilane monolayers - Giner, Ignacio; Torun, Boray; Han, Yan; Duderija, Belma; Meinderink, Dennis; Orive, Alejandro González; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Tiemann, Michael; Schmid, Hans-Joachim; Grundmeier, Guido (Applied Surface Science)
Monodisperse micron-sized silica particle monolayers deposited onto plasma-grown SiOx-ultra-thin films have been used as reference systems to investigate wetting, water adsorption and capillary bridge formation as a function of silica surface functionalization. 1H,1H, 2H,2H perfluorooctyltriethoxysil (FOTS) monolayers, have been deposited on the respective surfaces by means of chemical vapor deposition resulting in macroscopically low energy surfaces. X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) reflection absorption spectroscopy confirmed the monolayer formation. Water adsorption isotherms were studied by a combination of in-situ FTIR reflection spectroscopy and quartz crystal microbalance (QCM) while macroscopic wetting was analysed by contact angle measurements. The comparative data evaluation indicates that the macroscopic wetting behaviour was changed as expected, however, that water nanodroplets formed both at intrinsic defects of the FOTS monolayer and at the FOTS/SiOx interface. Capillary bridges of liquid water are dominantly formed in the confined particle contact areas and between surface asperities on the particles. The comparison of wetting, adsorption and capillary bridge formation shows that the hydrophobization of porous materials by organosilane monolayers leads to the formation of morphology dependent nanoscopic defects that act as sites for preferential capillary bridge formation.

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Aus Daten müssen Informationen werden - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Entwicklung von Einstellungen, Selbstwirksamkeitserwartungen und Stressbewertung in Bezug auf Inklusion bei angehenden Sportlehrkräften –Vorläufige Ergebnisse einer hochschuldidaktischen Interventionsstudie - Grimminger-Seidensticker, Elke; Lautenbach, F. (Professionalisierung in der Sportlehrer*innenbildung – Konzepte und Forschungen im Rahmen der Qualitätsoffensive Lehrerbildung)

Emprise normative et déprise suggérée : des inégalités sociales dans l’injonction au vieillir actif en Europe - Grimminger-Seidensticker, Elke; Aceti, M.; Vieille Marchiset, G.; Knobé, S. (Figures du vieillir et formes de déprise)

Körperunzufriedenheit, Angsterleben und Präferenzen didaktischer Inszenierungen im Sportunterricht der Grundschule - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia; Trojan, J. (Zeitschrift für sportpädagogische Forschung)

A corpus-based approach to the usage and acquisition of prepositions by learners of German as a foreign language: form vs. function. - Weber, Tassja (Widening the Scope of Learner Corpus Research. Selected papers from the fourth Learner Corpus Research Conference.)
Since its beginnings in the late 1980s, the field of Learner Corpus Research (LCR) has been continuously evolving and thereby widening its scope. LCR is rapidly closing gaps within its original scope by expanding on the languages, language mediums (spoken vs written) and learner types covered, and it is turning its attention to ever-emerging new research questions and phenomena which arise at the crossroads with neighboring disciplines. In fact, by embracing e.g. the latest technical developments in Natural Language Processing and Computer Science as well as by adopting state-of-the-art research methodologies used in Corpus Linguistics which include sophisticated statistical methods of data analysis, LCR is dipping into new interdisciplinary subjects with curiosity and expanding its research scope and methodological repertoire. This volume combines selected research papers from the 4th LCR conference hosted by Eurac Research in Bolzano/Bozen (Italy) in October 2017. All contributions in this volume build on the topics of previous LCR conference volumes, and enrich them with their research. The contributions are arranged thematically and refer to the following ve LCR topics: (1) analysis of learner data in spoken language, (2) analysis of learner data in corpora of other languages than English, (3) analysis of learner data of young learners, (4) LCR, language learning and pedagogical applications, and (5) LCR and automatic language modeling. The assembled papers introduce innovative research strands, present original data and research findings, and discuss latest desiderata within the five thematic focal points of the book.

Imke Leicht/Christine Löw/Nadja Meisterhans/Katharina Volk (Hrsg.), 2017: Material turn: Feministische Perspektiven auf Materialität und Materialismus. Opladen, Berlin, Toronto: Verlag Barbara Budrich. 205 Seiten. 29,90 Euro - Kostan, Anastassija (Verwandtschaftsverhältnisse – Geschlechterverhältnisse im 21. Jahrhundert)

Implementing a Real-time System on a Platform FPGA operated with ReconOS - Lienen, Christian

Excited‐State Kinetics of an Air‐Stable Cyclometalated Iron(II) Complex - Steube, Jakob; Burkhardt, Lukas; Päpcke, Ayla; Moll, Johannes; Zimmer, Peter; Schoch, Roland; Wölper, Christoph; Heinze, Katja; Lochbrunner, Stefan; Bauer, Matthias (Chemistry – A European Journal)

Creativity in data analysis through confrontation with anomalous data - Pollmeier, Pascal; Fechner, Sabine (The beauty and pleasure of understanding: engaging with contemporary challenges through science education. Electronic Proceedings of the ESERA 2019 Conference.)
Creativity is perceived to be one of the core competences to succeed in the modern world. It is connected to art, music, dancing, etc., but there is just little insight into the role of creativity in science. As data analysis plays a major role in science, creative thinking has to be used to form theories out of observations. This study uses models-of-data to represent the mental model of the students. Within models-of-data different observations and previous knowledge are linked through different types of links, e.g. causal links. The goal of this study was to examine the creative aspect of data evaluation in presence of anomalous data. The students were confronted with two experiments which contradicted each other with regard to the underlying theory. Afterwards the students were asked to decide about their favored theory and reasoning about their choice in their lab reports. The model-of-data, which was reconstructed from the lab reports of the students, was used to extract creative aspects in the mental modelling process. Furthermore, a pre-post-questionnaire on epistemological beliefs of the students was conducted. Students mostly acquired an unscientific view on epistemology in school. The question was whether the confrontation with anomalous data and the triggering of creative modelling processes have any influence on this. The results show that most students did not take anomalous data into account in their modelling processes. They did either not recognise or just ignore the data. Just a few students worked on their theory because of the new, contradictory data. The students working on their theory scored higher in the post-questionnaire, so a positive effect of creativity on scientific epistemology can be assumed. Thus, creativity obviously gets a part of science and should be taught in school science in order to make students aware of their own creative potential.
Keywords: epistemology; conceptual change; anomalous data

Jointly Learning from Social Media and Environmental Data for Typhoon Intensity Prediction - Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (K-CAP 2019: Knowledge Capture Conference)
Existing technologies employ different machine learning approaches to predict disasters from historical environmental data. However, for short-term disasters (e.g., earthquakes), historical data alone has a limited prediction capability. In this work, we consider social media as a supplementary source of knowledge in addition to historical environmental data. Further, we build a joint model that learns from disaster-related tweets and environmental data to improve prediction. We propose the combination of semantically-enriched word embedding to represent entities in tweets with their semantics representations computed with the traditional word2vec. Our experiments show that our proposed approach outperforms the accuracy of state-of-the-art models in disaster prediction.
Keywords: sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:simba ngonga simba zahera sherif solide limboproject opal group_aksw dice

LimesWebUI – Link Discovery Made Simple - Sherif, Mohamed; Pestryakova, Svetlana; Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (18th International Semantic Web Conference (ISWC 2019))
In this paper we present LimesWebUI, our web interface of Limes. Limes, the Link Discovery Framework for Metric Spaces, is a framework for dis- covering links between entities contained in Linked Data sources. LimesWebUI assists the end user during the link discovery process. By representing the link specifications (LS) as interlocking blocks, our interface eases the manual creation of links for users who already know which LS they would like to execute. How- ever, most users do not know which LS suits their linking task best and therefore need help throughout this process. Hence, our interface provides wizards which allow the easy configuration of many link discovery machine learning algorithms, that does not require the user to enter a manual LS. We evaluate the usability of the interface by using the standard system usability scale questionnaire. Our over- all usability score of 76.5 suggests that the online interface is consistent, easy to use, and the various functions of the system are well integrated.
Keywords: 2019 sys:relevantFor:infai group_aksw simba sherif kevin ngonga Svetlana slipo limes dice sage limbo opal

Fine-tuned BERT Model for Multi-Label Tweets Classification - Zahera, Hamada Mohamed Abdelsamee; A. Elgendy, Ibrahim; Jalota, Rricha; Sherif, Mohamed (Proceedings of the Twenty-Eighth Text REtrieval Conference, TREC 2019, Gaithersburg, Maryland, USA, November 13-15, 2019)
In this paper, we describe our approach to classify disaster-related tweets into multilabel information types (ie, labels). We aim to filter first relevant tweets during disasters. Then, we assign tweets relevant information types. Information types can be SearchAndRescue, MovePeople and Volunteer. We employ a fine-tuned BERT model with 10 BERT layers. Further, we submitted our approach to the TREC-IS 2019 challenge, the evaluation results showed that our approach outperforms the F1-score of median score in identifying actionable information.
Keywords: zahera elgendy jalota sherif dice

Do your Resources Sound Similar? On the Impact of Using Phonetic Similarity in Link Discovery - Ahmed, Abdullah Fathi Ahmed; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (K-CAP 2019: Knowledge Capture Conference)
An increasing number of heterogeneous datasets abiding by the Linked Data paradigm is published everyday. Discovering links between these datasets is thus central to achieving the vision behind the Data Web. Declarative Link Discovery (LD) frameworks rely on complex Link Specification (LS) to express the conditions under which two resources should be linked. Complex LS combine similarity measures with thresholds to determine whether a given predicate holds between two resources. State of the art LD frameworks rely mostly on string-based similarity measures such as Levenshtein and Jaccard. However, string-based similarity measures often fail to catch the similarity of resources with phonetically similar property values when these property values are represented using different string representation (e.g., names and street labels). In this paper, we evaluate the impact of using phonetics-based similarities in the process of LD. Moreover, we evaluate the impact of phonetic-based similarity measures on a state-of-the-art machine learning approach used to generate LS. Our experiments suggest that the combination of string-based and phonetic-based measures can improve the Fmeasures achieved by LD frameworks on most datasets.
Keywords: sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:ngonga ahmed sherif solide limboproject opal group_aksw dice

LSVS: Link Specification Verbalization and Summarization - Fathi Ahmed, Abdullah; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (24th International Conference on Applications of Natural Language to Information Systems (NLDB 2019))
An increasing number and size of datasets abiding by the Linked Data paradigm are published everyday. Discovering links between these datasets is thus central to achieve the vision behind the Data Web. Declarative Link Discovery (LD) frameworks rely on complex Link Specification (LS) to express the conditions under which two resources should be linked. Understanding such LS is not a trivial task for non-expert users, particularly when such users are interested in generating LS to match their needs. Even if the user applies a machine learning algorithm for the automatic generation of the required LS, the challenge of explaining the resultant LS persists. Hence, providing explainable LS is the key challenge to enable users who are unfamiliar with underlying LS technologies to use them effectively and efficiently. In this paper, we address this problem by proposing a generic approach that allows a LS to be verbalized, i.e., converted into understandable natural language. We propose a summarization approach to the verbalized LS based on the selectivity of the underlying LS. Our adequacy and fluency evaluations show that our approach can generate complete and easily understandable natural language descriptions even by lay users.
Keywords: 2019 sys:relevantFor:infai group_aksw simba sherif ngonga ahmed slipo limes dice sage limbo opal

Big POI data integration with Linked Data technologies - Athanasiou, Spiros; Giorgos, Giannopoulos; Damien, Graux; Nikos, Karagiannakis; Jens, Lehmann; Ngonga Ngomo, Axel-Cyrille; Kostas, Patroumpas; Sherif, Mohamed; Skoutas, Dimitrios (International Conference on Extending Database Technology 2019, EDBT19)
Point of Interest (POI) data constitute the cornerstone of any application, service or product even remotely related to our physical surroundings. From navigation applications to social networks, tourism, and logistics, we use POI data to search, communicate, decide and plan our actions. POIs are semantically diverse and spatio-temporally evolving entities, having geographical, temporal and thematic relations. Currently, integrating POI data to increase their coverage, timeliness, accuracy and value is a resource-intensive and mostly manual process, with no specialized software available to address the specific challenges of this task. In this paper, we present an integrated toolkit for transforming, linking, fusing and enriching POI data, and extracting additional value from them. In particular, we demonstrate how Linked Data technologies can address the limitations, gaps and challenges of the current landscape in Big POI data integration. We have built a prototype application that enables users to define, manage and execute scalable POI data integration workflows built on top of state-of-the-art software for geospatial Linked Data. The application abstracts and hides away the underlying complexity, automates quality-assured integration, scales efficiently for world-scale integration tasks and lowers the entry barrier for end-users. Validated against real-world POI datasets in several application domains, our system has shown great potential to address the requirements and needs of cross-sector, cross-border and cross-lingual integration of Big POI data.
Keywords: 2019 sys:relevantFor:infai group_aksw simba sherif ngonga lehmann slipo limes dice deer

Das Ich im Schatten der Methode. Eine Hinführung zum Potenzial autoethnograﬁschen Schreibens für die wissenschaftliche Praxis - Vochatzer, Stefanie; Engelmann, Sebastian (Journal der Schreibberatung (18) 2, S. 86–99)

Heterogeneity in Marginal Non-Monetary Returns to Higher Education - Kamhöfer, Daniel A; Schmitz, Hendrik; Westphal, Matthias (Journal of the European Economic Association)

The Creation of Illegal Migration in the German Confederation, 1815–1866 - Schubert, Michael (Journal of Borderlands Studies)

Effects of long-term psychodynamic psychotherapy on life quality in mentally disturbed children - Krischer, M.; Smolka, B.; Voigt, B.; Lehmkuhl, G.; Flechtner, H.; Franke, Sebastian; Hellmich, M.; Trautmann-Voigt, S. (Psychotherapy Research)

Rheinland-Kita-Studie: Inklusion von Kindern mit Behinderung in Tageseinrichtungen für Kinder. Abschlussbericht - Kißgen, R.; Austermühle, J.; Franke, Sebastian; Limburg, D.; Wöhrle, J.

Service growth by acquisition – An event study - Eggert, A.; Böhm, Eva; Akalan, R.; Gebauer, H. (9th BMM-EMAC Biennial International Conference on Business Market Management, Berlin)

„Die Flucht“ (1977) oder: Die wachsende Ratlosigkeit nach 1976 (Veröffentlichungen der Universität Paderborn)

Work in the Age of Intelligent Machines: The Rise of Invisible Automation - Klowait, Nils; Erofeeva, Maria (Philosophical Literary Journal Logos)
The article analyzes how an emerging form of automation may drastically transform contemporary employment dynamics. Recent breakthroughs in the field of artificial intelligence (AI) make it possible to automate both manual and mental non-standard tasks. The first part of the article traces the development of AI. Whereas classical algorithms required the creation of a hermetic environment for AI to thrive, modern neural network-based AI is capable of surviving in the chaotic realm occupied by humans. Based on an analysis of changes in the nature of AI, the authors distinguish between substitutive and supplemental automation. The former refers to a complete replacement of humans by machines, while the latter indicates a selective substitution of humans in specific professional functions. In order to conceptualize professions as a nexus of automatable components, the authors employ Goffman’s dramaturgical framework. Goffman studied the social visibility of professional activity. Goffman held that any profession can be divided into invisible routines that are fundamental to it and a dramatization that makes the profession socially visible. The article demonstrates that the current utopian and antiutopian views of automation both reduce work to its visible components and neglect the logic of supplemental automation. The authors argue that the targets of modern automation are not the socially visible components but the invisible routines. In the final section, the authors develop a model that takes these invisible professional routines into account and analyze what effect this new type of automation may have on different types of professions with differing degrees of social visibility.
Keywords: Literature and Literary Theory; Philosophy; Cultural Studies

Exploring the link between payment schemes and customer fraud: a mental accounting perspective - Garnefeld, Ina; Eggert, Andreas; Husemann-Kopetzky, Markus; Böhm, Eva (Journal of the Academy of Marketing Science)
Keywords: Marketing; Economics and Econometrics; Business and International Management

Federal Judge Ideology: A New Measure of Ex Ante Litigation Risk - HUANG, ALLEN; HUI, KAI WAI; Li, Reeyarn (Journal of Accounting Research)
ABSTRACT Drawing on the political theory of judicial decision making, our paper proposes a new and parsimonious ex ante litigation risk measure: federal judge ideology. We find that judge ideology complements existing measures of litigation risk based on industry membership and firm characteristics. Firms in liberal circuits (the third quartile in ideology) are 33.5% more likely to be sued in securities class action lawsuits than those in conservative circuits (the first quartile in ideology). This result is stronger after the U.S. Supreme Court's ruling in the Tellabs case. We next show that the effect of judge ideology on litigation risk is greater for firms with more sophisticated shareholders and with higher expected litigation costs. Furthermore, judicial appointments affect litigation risk and the value of firms in the circuit, highlighting the economic consequences of political appointments of judges. Finally, using our new measure, we document that litigation risk deters managers from providing long‐term earnings guidance, a result that existing measures of litigation risk cannot show.
Keywords: Economics and Econometrics; Finance; Accounting

Effector-specific priming effects during action observation in combat sports. - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (German Journal of Exercise and Sport Research)

Processing head fakes in basketball: Are there ironic effects of instructions on the head-fake effect in basketball? - Güldenpenning, Iris; Weigelt, Matthias; Kunde, Wilfried (Human Movement Science)

Leveling up? An inter-neighborhood experiment on parochialism and the efficiency of multi-level public goods provision - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of Economic Behavior and Organization)
Keywords: Organizational Behavior and Human Resource Management; Economics and Econometrics

The power of active choice: Field experimental evidence on repeated contribution decisions to a carbon offsetting program - Kesternich, Martin; Römer, Daniel; Flues, Florens (European Economic Review)
Keywords: Economics and Econometrics; Finance

Analyse der Reibleistungsverteilung im Reifenlatsch unter Berücksichtigung der Fahrwerkdynamik eines Mehrlenkerachssystems zur Bewertung des Reifenverschleißes - Kohl, Sergej
Durch die Auslegung eines Fahrwerks werden maßgebend die Fahrsicherheit, der Fahrkomfort, die Effizienz und der Fahrspaß eines Kraftfahrzeugs bestimmt. Daher zählt das Fahrwerk zu den wichtigsten und zugleich komplexesten Systemen in einem Automobil. Aufgrund steigender Kundenanforderungen, Auflagen durch Gesetzgebung sowie Termin- und Kostendruck stellt die Entwicklung des Fahrwerks für die heutigen Automobile stets eine Herausforderung dar. Um die gestellten Anforderungen zu erfüllen, sind oftmals gegenläufige Maßnahmen erforderlich, sodass die Auslegung des Fahrwerks in der Regel nur einen Kompromiss bildet. Entwicklungsziele zur Reduktion der Umweltbelastung und zur Effizienzsteigerung gewinnen hierbei zunehmend an Bedeutung. Damit verbunden müssen die Interaktionen zwischen Fahrwerk und Reifen hinreichend genau erfasst werden, sodass folglich eine Erweiterung bisheriger Simulationsmethoden erforderlich ist. In der vorliegenden Arbeit wird eine Vorgehensweise mit dem Schwerpunkt auf der Abbildung der Wechselwirkungen zwischen der Fahrwerkdynamik am Beispiel einer Mehrlenkerhinterachse und des Reifen-Fahrbahn-Rollkontakts entwickelt, die eine modellbasierte Analyse der Reibvorgänge in der Kontaktzone unter realitätsnahen Bedingungen ermöglicht. Vor allem können dadurch die Auswirkungen der Fahrwerkauslegung auf die Leistungsübertragung zwischen Reifen und Fahrbahn und den resultierenden Reifenverschleiß effektiv bewertet und bereits in der frühen Entwicklungsphase berücksichtigt werden.
Keywords: Reifenverschleiß; Reibleistung; Reifenlatsch; Reifen-Fahrbahn-Kontakt; Fahrbahnanregung; Mehrlenkerachse; Kinematik; Elastokinematik; Fahrwerkdynamik; Frequenz- und Amplitudenabhängigkeit; Modellierung; Validierung; Mehrkörpersimulation; MKS; ADAMS; FTire

Zeiteffiziente messtechnische Analyse glatt-nichtlinearen Schwingverhaltens dynamischer Strukturen - Sprock, Christian
Die Bestimmung des Frequenzübertragungsverhaltens von Strukturen mit nichtlinearer Charakteristik ist eine im technischen Bereich vielfach auftretende Aufgabe, z.B. für die genaue Bestimmung dynamischer Eigenschaften in der Entwurfsphase oder bei der Parametrierung von Modellen. Die typisch angewandten Verfahren zur Schwingungsmessung solcher Strukturen legen in der Regel ein lineares Strukturverhalten zu Grunde, oder sie erfordern einen hohen Zeit- und Messaufwand für die Abbildung des nichtlinearen Verhaltens; häufig in Verbindung mit einer starken Belastung der zu testenden Struktur. Die Bestimmung nichtlinearen Strukturverhaltens ist somit oft nicht effizient realisierbar. In der vorliegenden Arbeit wird ein neuer Ansatz zur Schwingungsanalyse nichtlinearer Strukturen mit von der Anregungsamplitude abhängigem Übertragungsverhalten vorgestellt. Dabei liegt ein Schwerpunkt auf der messtechnischen Bestimmung des nichtlinearen Verhaltens bei deutlich reduziertem Zeit- bzw. Messaufwand. Das Verfahren basiert auf einer Messmethode, die eine effiziente Bestimmung des nichtlinearen Kennfeldes der analysierten Struktur mit speziellen multiharmonischen Anregungssignalen ermöglicht. In Kombination mit einem fortschrittlichen Auswertealgorithmus kann eine vollständige Beschreibung des dynamischen Verhaltens in Form eines charakteristischen Diagramms generiert werden. Das Messverfahren wird durch eine Identifikationsroutine ergänzt, die die erforderliche Anzahl an Messungen nochmals reduzieren kann. Es ist als Mess-System auf Hard- und Software implementiert; der Funktionsnachweis erfolgt an verschiedenen Beispielen.
Keywords: Schwingungsanalyse; nichtlineare Strukturdynamik; Multisinus; Duffing-Schwinger; amplitudenabhängige Nichtlinearität; Peakbending; Backbone Curve; Schwingungsmessung; Frequenzverstimmung; Autoregression; Best Linear Approximation

Modellierung und experimentelle Charakterisierung der Wechselwirkung zwischen Ultraschallwandler und Flüssigkeit in kavitationsbasierten Prozessen - Bornmann, Peter
Ultraschall wird zur Effizienzsteigerung in verfahrenstechnischen Prozessen eingesetzt. Die Betriebsparamter der Ultraschallsysteme werden empirisch ermittelt, da derzeit keine systematische Analyse der Wechselwirkung zwischen Ultraschallwandler und Schallfeld sowie kein Verfahren zur Messung der Kavitationsaktivität ohne zusätzlichen Sensor existieren. Auf Basis einer experimentellen Analyse des betrachteten sonochemischen Reaktors wird ein Finite-Elemente-Modell aufgebaut, das die Wechselwirkung zwischen Schallfeld und Ultraschallwandler berücksichtigt. Die modellbasierte Analyse zeigt, dass wegen der akustischen Eigenschaften des Autoklavs nur direkt an der Sonotrode Kavitation entsteht. Die Wechselwirkung zwischen Ultraschallwandler und Schallfeld ermöglicht Aussagen über das Schallfeld und die Kavitationsaktivität auf Basis der Rückwirkung auf den Ultraschallwandler. Die lineare Schalldruckverteilung ermöglicht eine Prognose über die Verteilung von Kavitationszonen. Das beschriebene Modell liefert wertvolle Erkenntnisse für die Auslegung, Analyse und Skalierung sonochemischer Reaktoren. Auf Grund der rauen Prozessrandbedingungen ist die Applikation von Sensoren zur Überwachung der Kavitationsaktivität in vielen sonochemischen Prozessen nicht möglich. Zur prozessbegleitenden Messung der Kavitationsaktivität wird ein Verfahren entwickelt, das die Bewertung der Kavitationsaktivität durch Auswertung der Rückwirkung auf den Ultraschallwandler erlaubt. Das Messverfahren ermöglicht eine vorhersagbare und reproduzierbare Durchführung kavitationsbasierter Prozesse und stellt eine wichtige Erweiterung für bestehende und neue Ultraschallsysteme dar.
Keywords: Sonochemie; Akustische Kavitation; Kavitationsmessung; Kavitationsdetektion; FEM-Simulation Ultraschallwandler; Prozessüberwachung; FEM-Simulation Schallfeld; Self-Sensing; Piezoelektrische Ultraschallwandler; Ultraschallreinigung

Klimaabkommen von Paris: Die vereinbarten dynamischen Anreize wirken kontraproduktiv - Gallier, Garlo; Kesternich, Martin; Sturm, Bodo

NRW-Sportschule: eine Längsschnittstudie zu Freizeitaktivität, chronischem Stress und Selbstkonzept - Breithecker, Jennifer; Kehne, Miriam (Zeitschrift für sportpädagogische Forschung)

Motorische Basiskompetenzen - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (German Journal of Exercise and Sport Research)
In der Sportwissenschaft existiert eine Vielzahl von motorischen Testinstrumenten, deren Konstruktionen unterschiedliche Zielstellungen verfolgen. Mit MOBAK-3-4 (Motorische Basiskompetenzen) etabliert sich ein kompetenzorientiertes Testverfahren für Dritt- und Viertklässler. In der vorliegenden Untersuchung mit N = 344 Kindern (167 Mädchen; M = 8,78 Jahre, SD = 0,40) sollen die faktorielle Validität des MOBAK-3-4 Testinstruments sowie Zusammenhänge mit dem Geschlecht, Alter und Gewichtsstatus (Body Mass Index, BMI), der Häufigkeit und Art von außerschulischer Sportaktivität sowie dem fähigkeitsorientierten Hagedorn-Parcours aufgeklärt werden. Die zweifaktorielle Struktur des MOBAK-3-4 konnte mit den Faktoren Sich-Bewegen und Etwas-Bewegen bestätigt werden (CFI = 0,97; RMSEA = 0,033). Zusammenhänge mit den motorischen Basiskompetenzen konnten durch die Integration der Kovariaten Geschlecht, Alter und BMI sowie Häufigkeit und Art von außerschulischer Sportaktivität in die konfirmatorische Faktorenanalyse nachgewiesen werden. Jungen zeigten gegenüber Mädchen im Umgang mit dem Ball (Etwas-Bewegen) bessere Leistungen. Mädchen waren hinsichtlich der Ganzkörperkoordination im Raum (Sich-Bewegen) leicht überlegen. Während die älteren Kinder im Etwas-Bewegen stärker als die jüngeren Kinder waren, zeigten sich im Sich-Bewegen keine altersspezifischen Leistungsunterschiede. Weiterhin stand die Häufigkeit Mannschaftssport in einem engen Zusammenhang mit Etwas-Bewegen sowie die Ausübung von Individualsportarten mit Sich-Bewegen. Zudem zeigten die Ergebnisse des Hagedorn-Parcours auf latenter Ebene mittlere bis starke Zusammenhänge mit den Kompetenzbereichen Sich-Bewegen (β = 0,75, p < 0,001) und Etwas-Bewegen (β = 0,66, p < 0,001).

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : Whereas many studies addressed the relation between acute physical exercise and executive functions (EF) in children, the effects of various modalities of acute exercise on EF still remain unclear. This systematic review investigated the effects of exercise with low and high cognitive demands on speed of processing and accuracy of performance in tasks examining inhibition, working memory, and cognitive flexibility in children. Method : A systematic literature research in electronic databases was performed. Controlled trials assessing the effects of acute exercise on EF in a pre–post design were included. Results : Ten studies involving a total of 890 participants revealed positive effects in working memory performance in speed of processing after acute exercises with low cognitive demands compared with seated rest, mixed results for inhibition after exercises with low and high cognitive demands, and mixed results for cognitive flexibility with low cognitive demands. Concerning accuracy, only mixed results were found for inhibition after exercises with low and high cognitive demands. Conclusion : The differentiated effects of acute exercises with low and high cognitive demands led to more positive effects in speed of processing compared with accuracy of performance. Further investigations including assessment of neurophysiological parameters of EF are needed.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review. - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatr Exerc Sci)

Entstehen durch eine Blicktäuschung Kosten für den Angreifer? - Güldenpenning, Iris; Weigelt, Matthias; Kunde, W. (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Die Blicktäuschung im Basketball: Einfluss des zeitlichen Versatzes zwischen Blick- und Kopfwendung auf den Täuschungseffekt - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Deceptive Actions - Güldenpenning, Iris; Weigelt, Matthias (Dictionary of Sport Psychology)

Impact of multi-dimensional vibration trajectories on quality and failure modes in ultrasonic bonding - Schemmel, Reinhard; Eacock, Florian; Dymel, Collin; Hemsel, Tobias; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (International Symposium on Microelectronics)
Ultrasonic joining is a common industrial process. To build electrical connections in the electronics industry, uni-axial and torsional ultrasonic vibration have been used to join different types of workpieces for decades. Many influencing factors like ultrasonic power, bond normal force, bond duration and frequency are known to have a high impact on bond quality and reliability. Multi-dimensional bonding has been investigated in the past to increase ultrasonic power and consequently bond strength. This contribution is focused on the comparison of circular, multi-frequency planar and uniaxial vibration trajectories used for ultrasonic bonding of copper pins on copper substrate. Bond quality was analyzed by shear tests, scanning acoustic microscopy and interface cross-sections.